2004
DOI: 10.1016/j.pain.2004.05.014
|View full text |Cite
|
Sign up to set email alerts
|

c-fos and CRF receptor gene transcription in the brain of acetic acid-induced somato-visceral pain in rats

Abstract: We aimed to characterize neuronal and corticotrophin-releasing (CRF) pathways in a model of somato-visceral pain in rats. Male rats received an intraperitoneal (i.p.) injection of either vehicle (controls) or acetic acid (AA) and were sacrificed 1, 2, 3, 4, or 6 h later. Coronal frozen sections of the brain were cut and mRNAs encoding the rat c-fos, CRF(1), CRF(2 alpha,beta) receptors were assayed by in situ hybridisation histochemistry. Localization of these transcripts within CRF-immunoreactive (i.r.) neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 57 publications
1
31
0
Order By: Relevance
“…Previous electrophysiologycal [6], biochemical [43][44][45] and behavioral findings [18,27] have suggested that amygdaloid CRF receptors are involved in nociceptive modulation. The microinjection of a nonselective antagonist of CRF receptors in the amygdala reversed the hyperalgesia induced by opioid withdrawal as evaluated by the tail flick test in rats [27].…”
Section: Discussionmentioning
confidence: 99%
“…Previous electrophysiologycal [6], biochemical [43][44][45] and behavioral findings [18,27] have suggested that amygdaloid CRF receptors are involved in nociceptive modulation. The microinjection of a nonselective antagonist of CRF receptors in the amygdala reversed the hyperalgesia induced by opioid withdrawal as evaluated by the tail flick test in rats [27].…”
Section: Discussionmentioning
confidence: 99%
“…The use of C-Fos expression as a marker of neuronal activation has shown that somatovisceral Sinniger, et al 2004;2005), and visceral (Wang, et al 2009) pain as well as stress-or abdominal surgery-induced GI disturbances (Bonaz and Tache 1994a;1994b;1997;Bonaz and Rivest 1998) and colitis ) induced the activation of the amygdala. In addition, the amygdala is one of the central areas from where digestive sensations are elicited in epileptic patients (Mulak, et al 2008) during intracerebral electrical stimulations.…”
Section: Amygdala and Visceral Hyperalgesiamentioning
confidence: 99%
“…PVN), the bed nucleus of the stria terminalis, the lateral septum, the thalamus, the periacqueductal gray, the PB, the LC, the raphe nuclei, and the dorsal vagal complex (area postrema, nucleus tractus solitarius and DMNV) (Knapska, et al 2007). All these regions have been shown to be activated in experimental models of stress, inflammation, and pain as represented by c-fos expression and/or CRF receptor mRNA induction (Bonaz and Tache 1994a;Bonaz and Rivest 1998;Porcher, et al 2004;Sinniger, et al 2004;2005) or electrical stimulations (Mulak, et al 2008). …”
Section: The Alteration Of Amygdala Control In Ibsmentioning
confidence: 99%
“…Previous biochemical (Sinniger et al, 2004;Greenwood-Van Meerveld et al, 2006;Ulrich-Lai et al, 2006) and behavioral (Lariviere and Melzack, 2000;McNally and Akil, 2002) studies point to the amygdala as an important site of CRF-mediated pain modulation, but the role of endogenously activated CRF1 and CRF2 receptors in the amygdala is not known. The present study used a multidisciplinary approach at the system and cellular levels to determine the effects of selective CRF1 and CRF2 receptor antagonists on pain-related synaptic facilitation in the amygdala, the underlying mechanisms and behavioral consequences.…”
Section: Introductionmentioning
confidence: 99%